Preparation method of titanium dioxide pigment for regenerated polyolefin and prepared titanium dioxide
By coating silicon oxide, zirconium oxide, aluminum phosphate and boehmite-type alumina film layers in titanium dioxide pigments and carrying out organic coating treatment, the existing titanium dioxide pigments are solved by heat resistance, light resistance and weather resistance in regenerated polyolefin resins. The problem of insufficient performance achieves higher whiteness and better weather resistance, extending service life.
Patent Information
- Application Number
- CN202411255450.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing titanium dioxide pigments have insufficient heat resistance, light resistance and weather resistance in regenerated polyolefin resins, which cannot meet the needs of use.
Using 20-24 wt% rutile titanium dioxide primary slurry, the coating of silicon oxide, zirconium oxide, aluminum phosphate and boehmite alumina film layers, and organic coating treatment is carried out to control the coating temperature and pH deposition. velocity, dense film layers are formed to improve oxidation resistance, UV resistance and light resistance.
The whiteness of titanium dioxide pigment in recycled polyolefin plastic system is significantly improved, the yellowing is reduced, the weather resistance is enhanced, the service life is extended, and the addition is reduced by 5-8% under the same conditions.
Smart Images

Figure BDA0005033908970000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of titanium dioxide preparation methods, and more specifically, to a method for preparing titanium dioxide pigment for recycled polyolefins and the prepared titanium dioxide. Background Art
[0002] Recycled plastics refer to plastic raw materials obtained by processing waste plastics through physical or chemical methods such as pretreatment (screening, classification, cleaning), melt granulation, modification, etc. It is the reuse of plastics. According to the characteristics of the materials, recycled plastics are mainly thermoplastic polyolefin products such as PP and PE, which are also the most common plastic packaging film materials.
[0003] In order to improve the heat resistance, light resistance and weather resistance of recycled plastic products, especially polyolefins and other easily yellowing resins, and to increase their service life, it is necessary to add titanium dioxide pigment (also known as titanium dioxide). At the same time, it can also effectively optimize the mechanical and electrical properties of plastic products.
[0004] After testing the following currently available titanium dioxide products mixed with PP resin, it was found that: the general rutile titanium dioxide used has poor temperature resistance, and its yellowing index is as high as 3.15; the rutile titanium dioxide used in plastics has a yellowish hue and a low whiteness of 93.78; the weather resistance of anatase titanium dioxide is very poor, and its light stability ΔE is as high as 2.56, which is insufficient and cannot meet its use needs. Summary of the invention
[0005] In order to improve the whiteness of titanium dioxide pigment in recycled polyolefin resin system, reduce yellowing and improve weather resistance, the present application provides a method for preparing titanium dioxide pigment for recycled polyolefin and the prepared titanium dioxide.
[0006] In the first aspect, the present application provides a method for preparing titanium dioxide pigment for recycled polyolefins, using the following technical solution: A method for preparing titanium dioxide pigment for regenerated polyolefins comprises the following steps: S1, using a rutile titanium dioxide primary slurry with a concentration of 20-24wt% and a particle size of 0.15-0.25μm as a raw material, coating a silicon oxide film at 70-85°C, coating a zirconium oxide film at 60-70°C, and then coating an aluminum phosphate film and a boehmite aluminum oxide film at 50-65°C respectively; S2, and then filtered, washed, dehydrated, dried, air flow crushed, and then organic coating treatment is performed to obtain.
[0007] By adopting the above technical solution: S1 uses low titanium dioxide concentration slurry as raw material, different coating temperatures, special coating formula combination, and limits the type of coating layer, so that the resulting product has anti-oxidative degradation, yellowing and better weather resistance in the recycled polyolefin plastic system. Among them, (1) first coat a layer of low-content amorphous silicon dioxide film to block lattice defects, shield the light activation points on its surface, improve the antioxidant and UV resistance, and limit the coating to a higher temperature of 70-85°C, and adjust the deposition rate at a slower pH value to make the silicon oxide film more dense; (2) coat a small amount of zirconium dioxide film to enhance weather resistance and improve product brightness, and limit the coating to a higher temperature of 60-70°C, and maintain the pH deposition rate at a slower flow, so that the zirconium oxide film is dense; (3) coat a layer of aluminum phosphate film to improve the light resistance and yellowing resistance of titanium dioxide, add the coating agent at one time, and use sodium aluminate and aluminum sulfate to slowly adjust the pH deposition rate; (4) coat a layer of low-content boehmite aluminum oxide to enhance gloss and improve product dispersibility; limit the coating to a lower temperature of 50-60°C, and directly use sodium aluminate and aluminum sulfate to slowly adjust the pH deposition rate.
[0008] S2 is treated with organic coating to enhance the compatibility, dispersibility and processing fluidity of the product in the polyolefin plastic system, and finally to meet the requirements of the titanium dioxide pigment product used in recycled polyolefin plastic resin.
[0009] Optionally, the preparation method of the primary slurry is: add the primary rutile titanium dioxide to water for slurry dispersion, adjust the pH to 9.3-9.8, and obtain a slurry containing a titanium dioxide concentration of 35-38wt%; then add a sodium silicate aqueous solution, disperse, grind and sieve, control the slurry particle size to 0.15-0.25μm, add water to adjust the system titanium dioxide concentration to 20-24wt%, and adjust the pH to 9.8-10.8, so as to obtain the primary slurry; The sodium silicate aqueous solution has a concentration of 160-180 g / L in terms of SiO2, and the added amount in terms of SiO2 accounts for 0.3-0.4% of the amount of TiO2.
[0010] By adopting the above technical solution: controlling the beating, dispersion, grinding and particle size range, firstly, controlling the slurry with a higher titanium dioxide concentration of 35-38wt% during beating, which is beneficial to improving the grinding effect; adding sodium hydroxide solution to adjust the pH of the slurry to 9.3-10.8 can keep the slurry in a well-dispersed state.
[0011] Optionally, the coating method of the silicon oxide film layer is: Under the conditions of temperature of 70-85°C and stirring speed of 55-65rpm, sodium silicate aqueous solution is added to the primary slurry for dispersion, the pH is first adjusted to 9.3-9.6 and then reacted for 30-40min, and then the pH is adjusted to 6.9-7.5 and matured for 70-100min to obtain a silicon oxide film layer; the sodium silicate aqueous solution has a concentration of 95-120g / L in terms of SiO2, and the amount added is 1-1.5% of the weight of TiO2 in terms of SiO2.
[0012] By adopting the above technical solution: under the above conditions, a dense amorphous silicon oxide film layer is formed on the surface of titanium dioxide to block lattice defects, shield the light activation points on its surface, and improve the anti-oxidation and anti-ultraviolet performance.
[0013] Optionally, the coating method of the zirconium oxide film layer is: The slurry coated with the silicon oxide film layer is cooled to 60-70°C, and a zirconium oxychloride aqueous solution is added dropwise within 110-130 minutes at a stirring speed of 65-80 rpm, and a sodium hydroxide aqueous solution is added in parallel to adjust the slurry pH to 8.2-9.5, react for 30-40 minutes, and then adjust the pH to 8.0-8.3, and mature for 50-70 minutes to obtain a zirconium oxide film layer; The concentration of the zirconium oxychloride aqueous solution is 110-130 g / L in terms of ZrO2, and the added amount is 0.25-0.35% of the weight of TiO2 in terms of ZrO2.
[0014] By adopting the above technical solution: under the above conditions, a small amount but dense zirconium oxide film coating is completed.
[0015] Optionally, the coating method of the aluminum phosphate film layer is: Keep the temperature of the slurry coated with the zirconium oxide film layer, add the sodium hexametaphosphate aqueous solution at a stirring speed of 50-60rpm, disperse for 30-40min, add the sodium metaaluminate aqueous solution within 45-65min, and add the aluminum sulfate solution in parallel to adjust the pH value of the slurry to 9.4-9.8, mature for 20-30min, then add the aluminum sulfate solution to adjust the pH value of the slurry to 6.0-6.3, mature for 20-30min, and obtain the aluminum phosphate film layer; The sodium hexametaphosphate aqueous solution has a concentration of 140-180 g / L in terms of P2O5, and the amount added is 1.0-1.5% of the weight of TiO2 in terms of P2O5; The sodium aluminate aqueous solution has a concentration of 110-130 g / L in terms of Al2O3; The aluminum sulfate solution has a concentration of 85-100 g / L in terms of Al2O3.
[0016] Optionally, the coating method of the boehmite aluminum film layer is: The temperature of the slurry coated with the aluminum phosphate film layer is adjusted to 50-60°C, and at a stirring speed of 55-65rpm, a sodium aluminate aqueous solution is added for 30-50min, and an aluminum sulfate solution is added in parallel to adjust the pH of the slurry to 7.0-8.5, and then matured for 40-60min, and then adjusted to 6.8-7.2, and then matured for 2-2.5h to obtain a boehm-type aluminum film layer; The sodium aluminate aqueous solution has a concentration of 85-120 g / L in terms of Al2O3, and the added amount is 0.5-0.7% of the weight of TiO2.
[0017] Optionally, after filtering, washing, dehydrating and drying the slurry after the boehm type aluminum oxide film layer, the resistivity is controlled to be 80-120Ω·m and the water content is ≤0.3%.
[0018] Optionally, the specific method of the organic coating treatment is: adding an organic coating agent at the outlet of the steam powder machine for organic coating treatment, and the added amount is 0.25-0.45% of the weight of TiO2.
[0019] Optionally, the organic coating agent is one of dimethyl silicone oil, trimethylolethane, polysilanol, and octyltriethoxysilane.
[0020] In a second aspect, the present application provides a titanium dioxide powder prepared by the above-mentioned method for preparing titanium dioxide pigment for recycled polyolefin.
[0021] By adopting the above technical solution, compared with the existing products, it not only meets the special performance requirements, the addition amount can be reduced by 5-8% under the same conditions, but also the service life of the polyolefin product is increased by 2-3 times.
[0022] In summary, this application has the following beneficial effects: 1. This application adopts a lower titanium dioxide slurry concentration as raw material, different coating temperatures, limited coating layer types, and different coating times and pH values, so that the resulting product has anti-oxidative degradation, yellowing and better weather resistance in the application of recycled polyolefin plastic system; and then performs organic coating treatment to enhance the compatibility, dispersibility and processing fluidity of the product in the polyolefin plastic system, and finally obtains a titanium dioxide pigment product that meets the requirements of application in recycled polyolefin plastic resin; 2. The present application performs coating under different coating temperatures, lower coating agent concentrations, different stirring intensities, and different coating times and pH values, so as to form low-content but dense silicon oxide and zirconium oxide film layers, as well as special aluminum phosphate and boehmite-type aluminum oxide film layers. DETAILED DESCRIPTION
[0023] The present application is further described in detail below with reference to the embodiments.
[0024] The physical parameters of the initial product of rutile titanium dioxide produced by the sulfuric acid process are: L value 94%, b value 3.5, titanium dioxide content 98%, rutile content 97.5%, particle size range 0.10-0.46μm, Fe impurity content 50ppm.
[0025] Example 1 A method for preparing titanium dioxide pigment for regenerated polyolefin comprises the following steps: S1. Preparation of primary slurry: add deionized water to 10 kg of rutile titanium dioxide primary product produced by sulfuric acid process for pulping and dispersion, add sodium hydroxide aqueous solution to adjust the system pH to 9.3, and obtain a slurry containing titanium dioxide concentration of 35wt%; then add sodium silicate aqueous solution (concentration is 160g / L in terms of SiO2, and the amount of sodium silicate added is 0.3% of the amount of TiO2 in terms of SiO2) and disperse for 30min, and grind by sand milling, screening and cyclone classification grinding and dispersion; take 50wt% titanium dioxide slurry with a particle size of 0.15-0.25μm, add water to adjust the system titanium dioxide concentration to 20wt%, and add sodium hydroxide aqueous solution to adjust the system pH to 9.8, and obtain the primary slurry; wherein the concentration of sodium hydroxide aqueous solution is 20wt%; Coating silicon oxide film layer: the primary slurry is heated to 70°C, and at a stirring speed of 55rpm, a sodium silicate aqueous solution (the concentration is 95g / L in terms of SiO2, and the amount of sodium silicate added is 1% of the weight of TiO2 in terms of SiO2) is added to the primary slurry for dispersion, hydrochloric acid is added dropwise within 130min to adjust the system pH to 9.3, and then react for 30min, and then hydrochloric acid is added to adjust the pH to 6.9, and then matured for 70min to obtain a silicon oxide film layer; wherein the hydrochloric acid concentration is 7wt%; Zirconium oxide film coating: the slurry coated with silicon oxide film is cooled to 60°C, and at a stirring speed of 65 rpm, a zirconium oxychloride aqueous solution (the concentration is 110 g / L in terms of ZrO2, and the amount of zirconium oxychloride added is 0.25% of the weight of TiO2 in terms of ZrO2) is added dropwise within 110 minutes, and a sodium hydroxide aqueous solution is added in parallel to adjust the system pH to 8.2, and then react for 30 minutes, and then hydrochloric acid is added to adjust the pH to 8.0, and then matured for 50 minutes to obtain a zirconium oxide film; wherein the concentration of the sodium hydroxide aqueous solution is 10wt%; the concentration of the hydrochloric acid is 7wt%; Coating aluminum phosphate film layer: maintain the slurry temperature after coating zirconium oxide film layer, add sodium hexametaphosphate aqueous solution (concentration is 140g / L in terms of P2O5, and the added amount is 1.0% of the weight of TiO2 in terms of P2O5) at a stirring speed of 50rpm, disperse for 30min, add sodium aluminate aqueous solution dropwise for 45min, add aluminum sulfate solution in parallel to adjust the system pH to 9.4, and then mature for 20min, then add aluminum sulfate solution to adjust the system pH to 6.0, and then mature for 20min, to obtain aluminum phosphate film layer; wherein the concentration of sodium aluminate aqueous solution is 110g / L in terms of Al2O3, and the concentration of aluminum sulfate solution is 85g / L in terms of Al2O3; Coating the boehm-type aluminum film layer: adjust the temperature of the slurry after coating the aluminum phosphate film layer to 50°C, add a sodium aluminate aqueous solution (the concentration is 85g / L in terms of Al2O3, and the amount added is 0.5% of the weight of Al2O3 to TiO2) at a stirring speed of 55rpm for 30min, and add an aluminum sulfate solution in parallel to adjust the system pH to 7.0 and mature for 40min, then add 10wt% hydrochloric acid to adjust the system pH to 6.8 and mature for 2h to obtain a boehm-type aluminum film layer; wherein the concentration of the aluminum sulfate solution is 85g / L in terms of Al2O3; S2. The slurry coated with the boehmite aluminum film layer is filtered, washed, dehydrated and dried in sequence to control its resistivity to 80-120Ω·m and its water content ≤0.3%. It is then air flow crushed and ground, and an organic coating agent is added at the outlet of the steam powder machine for organic coating treatment (octyltriethoxysilane, the addition amount is 0.3% of the weight of TiO2) to obtain titanium dioxide for recycled polyolefins.
[0026] Example 2 A method for preparing titanium dioxide pigment for regenerated polyolefin comprises the following steps: S1. Preparation of primary slurry: add deionized water to 10 kg of rutile titanium dioxide primary product produced by sulfuric acid process for pulping and dispersion, add sodium hydroxide aqueous solution to adjust the system pH to 9.5, and obtain a slurry containing titanium dioxide concentration of 37 wt%; then add sodium silicate aqueous solution (concentration is 170 g / L in terms of SiO2, and the amount of sodium silicate added is 0.35% of the amount of TiO2 in terms of SiO2) and disperse for 30 minutes, and grind and disperse by sand milling, screening and cyclone classification grinding; take 50 wt% titanium dioxide slurry with a particle size of 0.15-0.25 μm, add water to adjust the system titanium dioxide concentration to 22 wt%, and add sodium hydroxide aqueous solution to adjust the system pH to 10.3, and obtain the primary slurry; wherein the concentration of sodium hydroxide aqueous solution is 20 wt%; Coating silicon oxide film layer: the primary slurry is heated to 70°C, and at a stirring speed of 55 rpm, a sodium silicate aqueous solution (the concentration is 105 g / L in terms of SiO2, and the amount of sodium silicate added is 1.25% of the weight of TiO2 in terms of SiO2) is added to the primary slurry for dispersion, hydrochloric acid is added dropwise within 140 minutes to adjust the system pH to 9.5, and then react for 35 minutes, and then hydrochloric acid is added to adjust the pH to 7.2, and then matured for 85 minutes to obtain a silicon oxide film layer; wherein the hydrochloric acid concentration is 7wt%; Zirconium oxide film coating: the slurry coated with silicon oxide film is cooled to 65°C, and at a stirring speed of 70 rpm, a zirconium oxychloride aqueous solution (the concentration is 110 g / L in terms of ZrO2, and the amount of zirconium oxychloride added is 0.25% of the weight of TiO2 in terms of ZrO2) is added dropwise within 120 minutes, and a sodium hydroxide aqueous solution is added in parallel to adjust the system pH to 9.0, and then react for 35 minutes, and then hydrochloric acid is added to adjust the pH to 8.2, and then matured for 60 minutes to obtain a zirconium oxide film; wherein the concentration of the sodium hydroxide aqueous solution is 10wt%; the concentration of the hydrochloric acid is 7wt%; Coating aluminum phosphate film: maintain the temperature of the slurry after coating the zirconium oxide film, add sodium hexametaphosphate aqueous solution (concentration is 160g / L in terms of P2O5, and the added amount is 1.25% of the weight of TiO2 in terms of P2O5) at a stirring speed of 55rpm, disperse for 35min, drop sodium aluminate aqueous solution and, at the same time, add aluminum sulfate solution in parallel to adjust the system pH to 9.6 and mature for 25min, then add aluminum sulfate solution to adjust the pH to 6.2 and mature for 25min, to obtain the aluminum phosphate film; wherein the concentration of sodium aluminate aqueous solution is 120g / L in terms of Al2O3; the concentration of aluminum sulfate solution is 100g / L in terms of Al2O3; Coating the boehm-type aluminum film layer: adjust the temperature of the slurry after coating the aluminum phosphate film layer to 55°C, and at a stirring speed of 60rpm, drop a sodium aluminate aqueous solution (the concentration is 100g / L in terms of Al2O3, and the amount added is 0.6% of the weight of Al2O3 to TiO2) within 40min, and simultaneously add an aluminum sulfate solution in parallel to adjust the system pH to 8.0 and mature for 50min, then add 10wt% hydrochloric acid to adjust the system pH to 7.0 and mature for 2.2h to obtain a boehm-type aluminum film layer; wherein the concentration of the aluminum sulfate solution is 100g / L in terms of Al2O3; S2. The slurry coated with the boehmite aluminum film layer is filtered, washed, dehydrated and dried in sequence to control its resistivity to 80-120Ω·m and its water content to ≤0.3%. It is then air flow crushed and ground, and an organic coating agent (dimethyl silicone oil, added in an amount of 0.35% of the weight of TiO2) is added at the outlet of the gas powder machine for organic treatment to obtain titanium dioxide for recycled polyolefins.
[0027] Example 3 A method for preparing titanium dioxide pigment for regenerated polyolefin comprises the following steps: S1. Preparation of primary slurry: add deionized water to 10 kg of rutile titanium dioxide primary product produced by sulfuric acid process for pulping and dispersion, add 20 wt% sodium hydroxide aqueous solution to adjust the system pH to 9.8, and obtain a slurry containing 38 wt% titanium dioxide; then add sodium silicate aqueous solution (the concentration is 180 g / L in terms of SiO2, and the amount of sodium silicate added is 0.4% of the amount of TiO2 in terms of SiO2) and disperse for 30 minutes, and grind by sand milling, sieving and cyclone classification grinding and dispersion; take 50 wt% titanium dioxide slurry with a particle size of 0.15-0.25 μm, add water to adjust the system titanium dioxide concentration to 24 wt%, and add sodium hydroxide aqueous solution to adjust the system pH to 10.8, and obtain the primary slurry; Coating silicon oxide film layer: the primary slurry is heated to 85°C, and at a stirring speed of 65rpm, a sodium silicate aqueous solution (the concentration is 120g / L in terms of SiO2, and the amount of sodium silicate added is 1.5% of the weight of TiO2 in terms of SiO2) is added to the primary slurry for dispersion, hydrochloric acid is added dropwise within 150min to adjust the system pH to 9.6, and then react for 40min, and then hydrochloric acid is added to adjust the pH to 7.5 and mature for 100min to obtain a silicon oxide film layer; wherein the hydrochloric acid concentration is 8wt%; Zirconium oxide film coating: the slurry coated with silicon oxide film is cooled to 70°C, and at a stirring speed of 80 rpm, a zirconium oxychloride aqueous solution (the concentration is 130 g / L in terms of ZrO2, and the amount of zirconium oxychloride added is 0.30% of the weight of TiO2 in terms of ZrO2) is added dropwise within 130 minutes, and a sodium hydroxide aqueous solution is added in parallel to adjust the system pH to 9.5, and then react for 40 minutes, and then sodium hydroxide aqueous solution is added to adjust the pH to 8.3, and then matured for 70 minutes to obtain a zirconium oxide film; wherein the concentration of the sodium hydroxide aqueous solution is 10wt%; Coating aluminum phosphate film layer: maintain the slurry temperature after coating zirconium oxide film layer, add sodium hexametaphosphate aqueous solution (concentration is 160g / L in terms of P2O5, and the added amount is 1.0% of the weight of TiO2 in terms of P2O5) at a stirring speed of 60rpm, disperse for 40min, add sodium aluminate aqueous solution dropwise within 65min, and add aluminum sulfate solution in parallel to adjust the system pH to 9.8 and mature for 30min, then add aluminum sulfate solution to adjust the system pH to 6.3 and mature for 30min, to obtain aluminum phosphate film layer; wherein the concentration of sodium aluminate aqueous solution is 130g / L in terms of Al2O3; the concentration of aluminum sulfate solution is 95g / L in terms of Al2O3; Coating the boehm-type aluminum film layer: adjust the temperature of the slurry after coating the aluminum phosphate film layer to 60°C, add a sodium aluminate aqueous solution (the concentration is 120g / L in terms of Al2O3, and the amount added is 0.7% of the weight of Al2O3 to TiO2) within 50 minutes at a stirring speed of 65rpm, and add an aluminum sulfate solution in parallel to adjust the system pH to 8.5 and then mature for 60 minutes, then add 10wt% hydrochloric acid to adjust the system pH to 7.2 and then mature for 2.5h to obtain a boehm-type aluminum film layer; wherein the concentration of the aluminum sulfate solution is 95g / L in terms of Al2O3; S2. The slurry coated with the boehmite aluminum film layer is filtered, washed, dehydrated and dried in sequence to control its resistivity to 80-120Ω·m and its water content to ≤0.3%. It is then air flow crushed and ground, and an organic coating agent (polysilicone, added in an amount of 0.45% of the weight of TiO2) is added at the outlet of the gas powder machine for organic treatment to obtain titanium dioxide for recycled polyolefins.
[0028] Comparative Example 1 A general-purpose rutile titanium dioxide pigment, manufactured by Longbai Group Co., Ltd., model number 996.
[0029] Comparative Example 2 A rutile titanium dioxide pigment for plastics, manufactured by Panzhihua Oriental Titanium Co., Ltd., model R5568.
[0030] Comparative Example 3 An anatase titanium dioxide pigment, manufactured by Guangxi Jinmao Titanium Industry Co., Ltd., model JMA110.
[0031] Comparative Example 4 A titanium dioxide pigment, which is different from Example 1 in that the conditions for preparing the primary slurry and coating the boehmite aluminum film layer in step S1 are different, specifically as follows: S1. Preparation of primary slurry: add deionized water to 10 kg of rutile titanium dioxide primary product produced by sulfuric acid process for pulping and dispersion, add sodium hydroxide aqueous solution to adjust the system pH to 9.3, and obtain a slurry containing titanium dioxide concentration of 30 wt%; then add sodium silicate aqueous solution (the concentration is 160 g / L in terms of SiO2, and the amount of sodium silicate added is 0.3% of the amount of TiO2 in terms of SiO2) and disperse for 30 minutes, and grind, screen and cyclone graded grinding and dispersion to control the slurry particle size within the range of 0.05-0.1 μm, add water to adjust the system titanium dioxide concentration to 18 wt%, and add sodium hydroxide aqueous solution to adjust the system pH to 9.8, and obtain the primary slurry; wherein the concentration of sodium hydroxide aqueous solution is 20 wt%; Coating silicon oxide film layer: the primary slurry is heated to 65°C, and at a stirring speed of 55 rpm, a sodium silicate aqueous solution (the concentration is 95 g / L in terms of SiO2, and the amount of sodium silicate added is 1% of the weight of TiO2 in terms of SiO2) is added to the primary slurry for dispersion, hydrochloric acid is added dropwise within 130 minutes to adjust the system pH to 9.3, and then react for 30 minutes, and then hydrochloric acid is added to adjust the pH to 6.9 and mature for 70 minutes to obtain a silicon oxide film layer; wherein the hydrochloric acid concentration is 7wt%; Zirconium oxide film coating: the slurry coated with silicon oxide film was cooled to 55°C, and at a stirring speed of 65 rpm, an aqueous zirconium oxychloride solution (the concentration was 110 g / L in terms of ZrO2, and the amount of zirconium oxychloride added was 0.25% of the weight of TiO2 in terms of ZrO2) was added dropwise within 110 min. At the same time, an aqueous sodium hydroxide solution was added in parallel to adjust the system pH to 8.2, and the reaction was carried out for 30 min. After the pH was adjusted to 8.0 with hydrochloric acid, the slurry was aged for 50 min to obtain a zirconium oxide film; wherein the concentration of the aqueous sodium hydroxide solution was 10 wt%; the concentration of the hydrochloric acid was 7 wt%.
[0032] Comparative Example 5 A titanium dioxide pigment, which is different from Example 1 in that the conditions for preparing the primary slurry and coating the silicon oxide film layer in step S1 are different, specifically as follows: S1. Preparation of primary slurry: add deionized water to 10 kg of primary rutile titanium dioxide produced by sulfuric acid process for pulping and dispersion, add sodium hydroxide aqueous solution to adjust the system pH to 9.3, and obtain a slurry containing titanium dioxide concentration of 42 wt%; then add sodium silicate aqueous solution (the concentration is 160 g / L in terms of SiO2, and the amount of sodium silicate added is 0.3% of the amount of TiO2 in terms of SiO2) and disperse for 30 minutes, and grind by sand milling, screening and cyclone classification grinding and dispersion to control the slurry particle size within the range of 0.3-0.4 μm, add water to adjust the system titanium dioxide concentration to 26 wt%, and add sodium hydroxide aqueous solution to adjust the system pH to 9.8, and obtain the primary slurry; wherein the concentration of sodium hydroxide aqueous solution is 20 wt%; Coating silicon oxide film layer: the primary slurry is heated to 90°C, and at a stirring speed of 55rpm, a sodium silicate aqueous solution (the concentration is 95g / L in terms of SiO2, and the amount of sodium silicate added is 1% of the weight of TiO2 in terms of SiO2) is added to the primary slurry for dispersion, hydrochloric acid is added dropwise within 130min to adjust the system pH to 9.3, and then react for 30min, and then hydrochloric acid is added to adjust the pH to 6.9, and then matured for 70min to obtain a silicon oxide film layer; wherein the hydrochloric acid concentration is 7wt%; Zirconium oxide film coating: the slurry coated with silicon oxide film is cooled to 75°C, and at a stirring speed of 65 rpm, zirconium oxychloride aqueous solution (concentration is 110 g / L in terms of ZrO2, and the amount of zirconium oxychloride added is 0.25% of the weight of TiO2 in terms of ZrO2) is added dropwise within 110 minutes, and sodium hydroxide aqueous solution is added in parallel to adjust the system pH to 8.2, and then react for 30 minutes, and hydrochloric acid is added to adjust the pH to 8.0, and then mature for 50 minutes to obtain the zirconium oxide film; wherein the concentration of the sodium hydroxide aqueous solution is 10wt%; the concentration of the hydrochloric acid is 7wt%.
[0033] Performance Testing The titanium dioxide pigment (also called titanium dioxide) prepared in the examples and comparative examples was subjected to the following performance tests, and the test results are recorded in Table 1.
[0034] Detection Methods 1. Basic indicators: 4g of titanium dioxide pigment and 196g of PP resin were blended into a mixture and added to a HTW-500x2 horizontal injection molding machine to obtain a sample with a thickness of 2mm. The sample was tested using a CM-23d spectrophotometer to obtain L value, b value, whiteness and yellowing indexes.
[0035] 2. Filter Pressure Value (FPV) is measured by using a twin-screw extruder to mix the sample with linear low-density polyethylene (LLDPE) to make a 70% concentration masterbatch, adding natural resin to dilute it into a carrier mixture containing 14% titanium dioxide, and then testing it with a single-screw extruder. It is used to characterize the dispersibility of titanium dioxide. A smaller value indicates better dispersibility in the system.
[0036] 3. Light-resistant UV stability: 4g titanium dioxide pigment and 196g PP resin were blended into a mixture and added to a HTW-500x2 horizontal injection molding machine to make a plate to obtain a 2mm thick sample. The sample was tested with a CM-23d spectrophotometer to obtain L value, a value, b value, and whiteness. Then, the sample was placed in a UV aging box and irradiated in a 700W UV340 aging box for 4 hours. The L value, a value, b value, and whiteness were measured again. The difference between the two tests was ΔL, Δa, and Δb. According to ΔE=(ΔL 2 +Δa 2 +Δb 2 ) 1 / 2 The light aging color difference ΔE value was calculated.
[0037] 4. 250℃ temperature resistance: The titanium dioxide powder is pressed into a cake by a manual cake press to obtain a sample. The sample is first tested by a CM-23d spectrophotometer to measure the L value, a, b value and whiteness index respectively. Then, the sample is heated at a constant temperature of 250℃ in an electric blast drying oven for 20 minutes. After the sample is taken out and cooled, the L value, a, b value and whiteness index are measured again. The difference between the two tests is ΔL, Δa, Δb. According to ΔE=(ΔL 2 +Δa 2 +Δb 2 ) 1 / 2 The 250℃ temperature resistance color difference ΔE value was calculated.
[0038] Table 1 Performance test results As shown in Table 1, after the titanium dioxide products prepared in Examples 1-3 are blended with PP resin, their whiteness is as high as 94.36 and the yellowing is as low as 1.06, while the whiteness of the commercially available products is 91-93 and the yellowing can be as high as 3.15, indicating that their whiteness is low and the yellowing is large, which shows that the titanium dioxide pigment prepared in this application has higher whiteness and less yellowing when applied to the resin system. At the same time, the filter pressure value is smaller after comparative testing, and the color difference value after light aging and temperature resistance testing is smaller, indicating that the patented product has better dispersibility and weather resistance in the plastic system, and better meets the characteristics of recycled polyolefins for titanium dioxide pigments.
[0039] Comparing Example 1 and Comparative Examples 4-5, the difference between Comparative Examples 4-5 and Example 1 is that the performance of the titanium dioxide pigments prepared is reduced by using primary slurries of different concentrations and different particle size ranges as raw materials and coating the silicon oxide film layer and the zirconium oxide film layer at different temperatures.
[0040] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing titanium dioxide pigment for recycled polyolefin, characterized in that: The following steps are involved: S1, using a rutile titanium dioxide primary slurry with a concentration of 20-24wt% and a particle size of 0.15-0.25μm as a raw material, coating a silicon oxide film at 70-85°C, coating a zirconium oxide film at 60-70°C, and then coating an aluminum phosphate film and a boehmite aluminum oxide film at 50-65°C respectively; S2, and then filtered, washed, dehydrated, dried, air flow crushed, and then organic coating treatment is performed to obtain.
2. The method for preparing titanium dioxide pigment for recycled polyolefin according to claim 1, characterized in that: The preparation method of the primary slurry is as follows: adding the primary rutile titanium dioxide to water for slurry dispersion, adjusting the pH to 9.3-9.8, and obtaining a slurry containing a titanium dioxide concentration of 35-38wt%; then adding a sodium silicate aqueous solution for dispersion, grinding and sieving, controlling the slurry particle size to 0.15-0.25μm, adding water to adjust the system titanium dioxide concentration to 20-24wt%, and adjusting the pH to 9.8-10.8, and obtaining the primary slurry; The sodium silicate aqueous solution has a concentration of 160-180 g / L in terms of SiO2, and the amount added in terms of SiO2 accounts for 0.3-0.4% of the amount of TiO2.
3. The method for preparing titanium dioxide pigment for recycled polyolefin according to claim 1, characterized in that: The coating method of the silicon oxide film layer is: Under the conditions of temperature of 70-85°C and stirring speed of 55-65rpm, add sodium silicate aqueous solution to the primary slurry, disperse, adjust the pH to 9.3-9.6, react for 30-40min, adjust the pH to 6.9-7.5, and ripen for 70-100min to obtain a silicon oxide film layer; The sodium silicate aqueous solution has a concentration of 95-120 g / L in terms of SiO2, and the added amount in terms of SiO2 accounts for 1-1.5% of the weight of TiO2.
4. The method for preparing titanium dioxide pigment for recycled polyolefin according to claim 1, characterized in that: The coating method of the zirconium oxide film layer is: The slurry coated with the silicon oxide film layer is cooled to 60-70°C, and a zirconium oxychloride aqueous solution is added dropwise within 110-130 minutes at a stirring speed of 65-80 rpm, and a sodium hydroxide aqueous solution is added in parallel to adjust the slurry pH to 8.2-9.5, react for 30-40 minutes, and then adjust the pH to 8.0-8.3, and mature for 50-70 minutes to obtain a zirconium oxide film layer; The concentration of the zirconium oxychloride aqueous solution is 110-130 g / L in terms of ZrO2, and the added amount is 0.25-0.35% of the weight of TiO2 in terms of ZrO2.
5. The method for preparing titanium dioxide pigment for recycled polyolefin according to claim 1, characterized in that: The coating method of the aluminum phosphate film layer is: Keep the temperature of the slurry coated with the zirconium oxide film layer, add the sodium hexametaphosphate aqueous solution at a stirring speed of 50-60rpm, disperse for 30-40min, add the sodium metaaluminate aqueous solution within 45-65min, and add the aluminum sulfate solution in parallel to adjust the pH value of the slurry to 9.4-9.8, mature for 20-30min, then add the aluminum sulfate solution to adjust the pH value of the slurry to 6.0-6.3, mature for 20-30min, and obtain the aluminum phosphate film layer; The sodium hexametaphosphate aqueous solution has a concentration of 140-180 g / L in terms of P2O5, and the amount added is 1.0-1.5% of the weight of TiO2 in terms of P2O5; The sodium aluminate aqueous solution has a concentration of 110-130 g / L in terms of Al2O3; The aluminum sulfate solution has a concentration of 85-100 g / L in terms of Al2O3.
6. The method for preparing titanium dioxide pigment for recycled polyolefin according to claim 1, characterized in that: The coating method of the boehm type aluminum film layer is: The temperature of the slurry coated with the aluminum phosphate film layer is adjusted to 50-60°C, and at a stirring speed of 55-65rpm, a sodium aluminate aqueous solution is added for 30-50min, and an aluminum sulfate solution is added in parallel to adjust the pH of the slurry to 7.0-8.5, and then matured for 40-60min, and then adjusted to 6.8-7.2, and then matured for 2-2.5h to obtain a boehm-type aluminum film layer; The sodium aluminate aqueous solution has a concentration of 85-120 g / L in terms of Al2O3, and the added amount is 0.5-0.7% of the weight of TiO2.
7. The method for preparing titanium dioxide pigment for recycled polyolefin according to claim 1, characterized in that: After filtering, washing, dehydrating and drying the slurry coated with the boehm type aluminum oxide film, the resistivity is controlled to be 80-120Ω·m and the water content is ≤0.3%.
8. The method for preparing titanium dioxide pigment for recycled polyolefin according to claim 1, characterized in that: The specific method of the organic coating treatment is: adding an organic coating agent to the outlet of the steam powder machine for organic coating treatment, and the added amount is 0.25-0.45% of the weight of TiO2.
9. The method for preparing titanium dioxide pigment for recycled polyolefin according to claim 8, characterized in that: The organic coating agent is one of dimethyl silicone oil, trimethylolethane, polysilanol and octyltriethoxysilane.
10. A titanium dioxide, characterized in that: The titanium dioxide pigment for recycled polyolefin is prepared by the preparation method of titanium dioxide pigment for recycled polyolefin according to any one of claims 1 to 9.
